Grassroots Familialism?NGO Mobilization and Neoconservatism in Contemporary Turkey - Sevgi Adak (European Journal of Turkish Studies)
Familialism in contemporary Turkey has primarily been analysed as a crucial aspect of the social policy of the Justice and Development Party (Adalet ve Kalkınma Partisi – AKP) government. The incorporation of familialism into other policy areas has also received some attention. Less attention has been given, however, to the ‘civil’ channels through which this state-level familialism is supported and propagated. A network of family-oriented conservative NGOs has proliferated in the last decade, and this article looks at the campaigns they organize and the discourses they use to influence and foster familialism at the state level. Drawing on an analysis of a national platform of family-oriented conservative NGOs – the Turkey Family Platform – as well as a local association active in the province of Bursa, the article argues that this network of NGOs plays a crucial role in shaping and disseminating familialism under the AKP, functioning as civil channels of neoconservatism, not only at the national level but also increasingly in the provinces.